Research and Analysis on the Development of New Energy Vehicles in the Context of Low-Carbon Environmental Protection - Hang, Lei (International Journal of Natural Resources and Environmental Studies, 2024)
Driven by the global wave of low-carbon and environmental consciousness, the new energy vehicle industry is poised for unprecedented development opportunities. As environmental challenges become increasingly severe, governments worldwide have implemented a series of policies to encourage the research and promotion of new energy vehicles. These vehicles not only play a crucial role in alleviating environmental pressures but also foster technological innovation and the transformation of economic structures. This paper, from the perspective of low-carbon and environmental protection, examines the current development status and technological pathways of new energy vehicles, explores the impact of policy support and industry chain construction on their advancement, and provides a forecast of the market outlook. Through a thorough analysis, a better understanding of the role and significance of new energy vehicles in low-carbon environmental protection can be gained, offering scientific foundations for future policy-making and industrial development.